Space Capitalism How Humans will Colonize Planets, Moons, and Asteroids - Nelson, Peter Lothian (Palgrave Studies in Classical Liberalism,, 2018)
This book compares and contrasts the motivations, morality, and effectiveness of space exploration when pursued by private entrepreneurs as opposed to government. The authors advocate market-driven, private initiatives take the lead through enhanced competition and significant resources that can be allocated to the exploration and exploitation of outer space. Space travel and colonisation is analysed through the prism of economic freedom and laissez faire capitalism, in a unique and accessible book.